Improved determination of aluminum in serum and urine with use of a stabilized temperature platform furnace - Leung, FY; Henderson, AR (Clinical chemistry (Baltimore, Md.), 1982)
This method for determining aluminum in serum and urine is essentially free from matrix interference and gives a linear response with concentration to at least 500 micrograms/l. Use of a stabilized temperature platform (L'vov platform, Perkin-Elmer Corp.) to approach a "steady-state" temperature, addition of matrix modifiers [especially Mg(NO3)2], and the use of peak area integration all helped substantially diminish spectral interference. With the platform furnace, serum protein concentrations as great as 260 g/L did not interfere with the determination of Al. The within- and between-assay precision (CV) was less than or equal to 3.5% and less than or equal to 7.4%, respectively. Analytical recovery of Al added to serum ranged between 95 and 101% throughout the linear calibration range (to 500 micrograms/L), either when measured directly from the standard curve or by the method of standard additions. The reference interval for Al in 28 healthy subjects was 2-14 micrograms/L (mean 6.5, SD 4.1 micrograms/L), and for 130 patients on hemodialysis, 20-550 micrograms/L (mean 87.5, SD 62.5 micrograms/L).